Effectiveness of Electronic Customer Relationship Management, Electronic Service Quality, and Trust on Customer Loyalty at PT Bilah Baja Makmur Abadi - Sri Rezeki; Elisabeth Nainggolan; Kelly Huang; Hommy Dorthy Ellyany Sinaga; Petrus Loo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effects of electronic customer relationship management (e-CRM), electronic service quality, and trust on customer loyalty at PT Bilah Baja Makmur Abadi. The research employs a quantitative approach using a survey method with 167 customers as respondents. Data was collected through questionnaires and analyzed using multiple regression analysis to test the hypotheses. The findings reveal that e-CRM, electronic service quality, and trust each significantly influence customer loyalty both individually and when considered together. Specifically, e-CRM had the highest contribution to customer loyalty, followed by trust and electronic service quality. The research also found that these three factors, when combined, explain over 50% of the variance in customer loyalty. The study contributes to existing theories by linking traditional customer relationship management to modern digital practices and highlights the critical role of trust and service quality in driving customer loyalty in the digital era. The research provides valuable insights for businesses aiming to enhance customer loyalty through digital platforms and offers recommendations for future studies to explore additional factors such as customer satisfaction and brand image.